2019
DOI: 10.1097/md.0000000000016898
|View full text |Cite
|
Sign up to set email alerts
|

Finite element analysis of spiral plate and Herbert screw fixation for treatment of midshaft clavicle fractures

Abstract: Both spiral plate and Herbert screw fixations have been clinically adopted for treating midshaft displaced clavicle fractures. However, the biomechanical properties of the 2 implant fixations have not yet been thoroughly evaluated. Here we report the results of a finite element analysis of the biomechanical properties of midshaft clavicle fractures treated with Herbert screw and spiral plate fixation. Hebert screw fixation showed stress distribution similar to intact clavicle under all loading conditions, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 37 publications
1
9
0
Order By: Relevance
“…Therefore, some finite element studies recommend different types of plates, such as anterior plates, spiral plates, and superior plates with no screw holes above the fracture area. [ 17 , 18 , 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, some finite element studies recommend different types of plates, such as anterior plates, spiral plates, and superior plates with no screw holes above the fracture area. [ 17 , 18 , 20 , 21 ]…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, some finite element studies recommend different types of plates, such as anterior plates, spiral plates, and superior plates with no screw holes above the fracture area. [17,18,20,21] A comminuted MCF model was secured with a 7-hole titanium superior LCP, and FEA was performed between the with LSC model and without LSC model on top of the fracture site. The 7 stress measurement points represent the stress geometrically generated at the same point on the edge of the LCP hole.…”
Section: Discussionmentioning
confidence: 99%
“…In the viewpoint of biomechanics, the clavicle plate mainly provided stability in bending directions [26] . In this study, the comparative analysis of structural stiffness showed that the structural stiffness of the magnesium alloy plate was close to but slightly larger than that of the intact clavicle under the bending condition, followed by titanium alloy and stainless steel plates.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the properties of all types of materials were assumed to be homogeneous, isotropic, and linearly elastic. This assumption was made regarding previous studies [7,9,18,26,30] , which discussed the FE analysis of plate fixation to treat midshaft clavicle fractures. Although this assumption was slightly different from the actual conditions, we believe the conclusion of this study should be the same.…”
Section: Discussionmentioning
confidence: 99%
“… 20 In all loading cases, an arbitrary static total force/torsion of 100 N/1 Nm was equally distributed on the relevant surface nodes situated at the 15‐mm most distal part of the clavicle. The sternal end of the clavicle was fixed in translation and rotation to avoid rigid‐body modes 22 …”
Section: Methodsmentioning
confidence: 99%